1993
DOI: 10.1080/02626669309492665
|View full text |Cite
|
Sign up to set email alerts
|

Bank erosion and protection in the Niger delta

Abstract: A field study of erosion processes and local responses was carried out at representative sites of major soil groups in the Niger delta. The soils at these sites varied widely from plastic silty clays to silty sands of varying relative densities. Information on soil type, stratification and state of compaction together with tidal velocity distribution and pool level variation in river channels was used to establish predominant mechanics of erosion. The influence of vegetation on bank stability is dependent on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Local people in Nigeria have used indigenous plants to tackle bank and gully erosions. Abam ( 1993 ) carried out a study in the Niger Delta region of Nigeria, which led to the knowledge that river banks, where bamboo plants and raffia palms had been planted by local people, prevented the washing away of soil which causes bank erosions. These plants serve as current breakers for the water and over time, strengthen the materials that make up the river banks.…”
Section: Indigenous Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Local people in Nigeria have used indigenous plants to tackle bank and gully erosions. Abam ( 1993 ) carried out a study in the Niger Delta region of Nigeria, which led to the knowledge that river banks, where bamboo plants and raffia palms had been planted by local people, prevented the washing away of soil which causes bank erosions. These plants serve as current breakers for the water and over time, strengthen the materials that make up the river banks.…”
Section: Indigenous Knowledgementioning
confidence: 99%
“…The application of local methods to solve local problems in the community can be called soft technology. Soft technologies, which in this sense are community-led disaster risk reduction (DRR) approaches, are critical to disaster management at the local level (Abam 1993 ; Domfeh 2007 ). It involves the use of local laws and experiences to alter nature to promote human development and management of the society.…”
Section: ‘Hard’ or ‘Soft’ Technology For Indigenous Knowledge?mentioning
confidence: 99%
“…Because of their fibrous root, rhizome and extensive leaf systems, (1) they hold soil together and reduce hydraulic conductivity, and (2) their canopies intercept rain water and fibrous roots take-up large quantities of intercepted water and releases it through transpiration. Furthermore, they improve hydrological systems such as the wetlands (these in turn improve the storage of the excess water in the river) – altogether, over time, these indigenous ecological processes strengthen the local riparian biotic and abiotic diversity that make up the riverbanks and hydrological systems and thereby reduce the chances of a flood disaster (Abam 1993 ; Barbedo et al 2014 ; Brody et al 2007 ; Calder & Aylward 2006 ). This would mean that FRM approaches that support planting of the traditional ecological plants and related practices would be most suited to address the impacts and risks posed by floods.…”
Section: Discussionmentioning
confidence: 99%
“…g = Acceleration due to gravity. Co = a coefficient with 0.13 Abam and Omuso (1999), carried out a sensitivity analysis of various parameters in the above equation and concluded that the flow velocity is the most important variable followed by the unit weight of water.…”
Section: Hydrologicmentioning
confidence: 99%